2023
DOI: 10.3390/f14030645
|View full text |Cite
|
Sign up to set email alerts
|

Why Healthy Pine Seedlings Die after They Leave the Nursery

Abstract: Artificial regeneration is successful when high-performing seedlings are transported with care to the planting site, stored for a short period in an environment without desiccation or fungal growth, and planted in a deep hole, so roots are in contact with moist soil. One of the requirements for success is the ability to avoid common planting mistakes. Due, in part, to the use of container stock plus an increase in rainfall, the average first-year survival of pine seedlings (89%) in the southern United States i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 123 publications
(174 reference statements)
0
2
1
Order By: Relevance
“…De ning a threshold value above which the effect of MSP may be considered as practically signi cant requires expert knowledge and data on long-term plantation dynamics and economic value that were not available for our study. Previous studies performed on Pinus taeda L. (South et al, 2023) suggest that the bene t of MSP during the rainy years that we observed in our study was too small to substantially increase stand value at harvest and, therefore, could be considered as negligible.…”
Section: Recommendations Managementcontrasting
confidence: 58%
See 2 more Smart Citations
“…De ning a threshold value above which the effect of MSP may be considered as practically signi cant requires expert knowledge and data on long-term plantation dynamics and economic value that were not available for our study. Previous studies performed on Pinus taeda L. (South et al, 2023) suggest that the bene t of MSP during the rainy years that we observed in our study was too small to substantially increase stand value at harvest and, therefore, could be considered as negligible.…”
Section: Recommendations Managementcontrasting
confidence: 58%
“…These observations provide robustness to our results since our results apply to tree species that show a wide range of responses to summer drought. Similarly, due to the limited number of experimental sites, we were not able to observe any impacts of vegetation or soil type, although these factors are known to have primary effects on seedling response to MSP (South et al, 2023), and forest managers should use their own expert knowledge to translate the results of our study to speci c site conditions. In many European countries, 1-year-survival is used as a criterion to evaluate planting success, with a threshold value set between 80 and 90% (Mataruga et al, 2023).…”
Section: Recommendations Managementmentioning
confidence: 98%
See 1 more Smart Citation
“…Particularly, treatment C, representing under prime seedlings, exhibited a 15% higher loss compared to the other treatments. South et al [34] showed that for Pinus, many problems can justify the losses, for example in transportation or during the process of removing seedlings from…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest that seedlings with a sufficiently large root-collar diameter and a young age, regardless of seedling type, can grow taller than the surrounding vegetation more quickly. In a literature review, South et al [26] reviewed and discussed the various factors that govern the successes and failures of reforestation and restoration programs with healthy pine seedlings after leaving the nursery. With a focus on pine seedlings planted in the southern United States, the authors also listed non-nursery factors that have killed pine seedlings in North America, Africa, and Europe.…”
Section: Perpetual Readjustment Of the Plant Production Chain Of Tree...mentioning
confidence: 99%